Modelling the Challenges of Public Hospital Management: A 180-Degree Stakeholder Perspective - Ghasem Abedi; Seyedeh Fatemeh Jafary; maryam Khazaee-Pool (Journal of Mazandaran University of Medical Sciences)
Background and purpose: This study aims to examine the challenges within the management structures of public hospitals, particularly how these challenges impede the achievement of executive goals. If the consequences of these challenges are not adequately addressed, they may result in significant issues in the management of medical and hospital services. These issues could have a detrimental impact on various stakeholders, including patients, hospital staff, and administrators. Therefore, this research identifies the key administrative challenges faced by public hospitals from the perspective of multiple stakeholders and proposes potential solutions to improve hospital management and service delivery. Materials and methods: This mixed-method study (quantitative and qualitative) involved two primary groups: healthcare providers and hospital managers/senior professionals, including 14 senior staff from a public hospital. In the qualitative phase, semi-structured interviews were conducted to identify the challenges in public hospitals. In the quantitative phase, a questionnaire was developed based on the qualitative findings and the opinions of 363 experts. Exploratory factor analysis was performed using SPSS and AMOS software (version 24). Results: According to stakeholders, the challenges in managing public hospitals were identified across four key categories: financial, procedural and decision-making, human resources, and infrastructure. The results of the data analysis revealed that procedural and decision-making challenges had a coefficient of 0.89 with a significance level of 7.881; financial challenges had a coefficient of 0.79 with a significance level of 6.994; human resource challenges had a coefficient of 0.75 with a significance level of 6.641; and infrastructure challenges had a coefficient of 0.43 with a significance level of 3.807. Conclusion: The study results indicate that procedural and decision-making challenges in public hospitals are key factors significantly affecting the achievement of hospital operational goals and have a broad influence on other critical aspects of public hospital services, including patient satisfaction and service efficiency. Additionally, financial constraints, human resource limitations, and infrastructure challenges diminish hospitals' capacity to effectively meet patients' needs and organizational goals in both quantitative and qualitative terms, posing serious barriers to healthcare quality and accessibility.